Evaluación de la eficiencia del nopal (Opuntia ficus-indica) para la disminución de la turbidez del río Carrizal en época lluviosa - Terán Sánchez, Jorge Luis (2022)
The objective of the research was to evaluate the efficiency of the nopal (Opuntia ficus-indica) for the reduction of the turbidity of the Carrizal River in the rainy season. Nopal leaves were collected in Ambato city, extracting the mucilage, to obtain flour (8% solution) and polyelectrolyte (mixture with 96% ethanol) of nopal. A completely randomized design with three factors was applied: Coagulant (flour and polyelectrolyte), dose (10, 20 and 40 ml) and stirring speed (20, 40 and 60 RPM). A total of 18 treatments were generated, using aluminum sulfate as a control. The initial levels of turbidity were 194 NTU and for SST 572,13 mg/L of samples taken from the Carrizal River. Regarding the application of nopal flour, T7 presented a 78,89% removal of turbidity and a 78,77% removal of SST. While, the polyelectrolyte in T16 obtained 99,67% for turbidity and 99,65% for SST, these values being the highest during the application of both coagulants. Regarding the proposed hypothesis, T18 (40 ml and 60 RPM) removes the turbidity of the Carrizal river water by 95,61%, despite the fact that T16 (10 ml and 60 RPM) presented a better removal (99,67%), the suitability of T18 is suggested since its efficiency is not so far from T16. It is recommended to promote the use of the natural coagulant of nopal, in the form of polyelectrolyte